From Equations to Insights: Navigating the Canvas of Tumor Growth Dynamics - Jha, Anshuman; Sahani, Suresh Kumar; Jha, Aditya; Sahani, Kameshwar (MASALIQ, 2023)
This report delves into the pivotal role that differential equations play in the modeling of dynamic systems, with a specific emphasis on their utility within the domain to tumor growth modeling. Differential equations furnish a quantitative framework for understanding the complex dynamics inherent in the growth of tumors, thereby empowering the formulation of predictions, possible treatment measures and prolonged prognostic outcomes. In this report we embark upon an exploration of the historical origin of these equations, their associated classifications, features and their extensive deployment in multiple disciplines such as physics, biology, economics and computer science, though the primary emphasis is on the domain of tumor growth. Through the medium of two hypothetical case studies, employing Gompertz and Logistic Growth models, this report vividly illustrates the indispensable role of differential equations in the realm of clinical decision-making, the planning of treatment measures and in building a stable foundation for future endeavors. It concurrently explores the advantages of employing differential equations within the framework of tumor growth modeling, underscoring their mathematical precision, predictive efficacy, quantitative insights and historical success. Nevertheless, the report remains forthright in acknowledging the limitations of these models, particularly their tendency for simplifications, the neglect of spatially distributed information and their disregard for Stochastic Effects.